The reciprocal relationship between material factors and health in the life course: evidence from SHARE and ELSA - Rasmus Hoffmann; Hannes Kröger; Eduwin Pakpahan (European Journal of Ageing, 2018)
The widely established health differences between people with greater economic resources and those with fewer resources can be attributed to both social causation (material factors affecting health) and health selection (health affecting material wealth). Each of these pathways may have different intensities at different ages, because the sensitivity of health to a lack of material wealth and the degree to which health can influence economic resources may change. We study the relative importance, in terms of explanatory power, of social causation and health selection, comparing the transitions from childhood to adulthood and from adulthood to old age. We use retrospective survey data from ten European countries from the Survey of Health, Ageing and Retirement in Europe (SHARELIFE, n~=~18,734) and the English Longitudinal Study of Ageing (ELSA, n~=~6117), and structural equations models in a cross-lagged panel design. Material wealth and health depend on their prior status, wealth more so than health. In the transition from childhood to adulthood, social causation and health selection are equally important: the standardized coefficients for men in SHARE are 0.07 and 0.06, respectively, i.e. one standard deviation increase in material wealth in childhood is associated with a 0.07 standard deviation increase in adult health. In the transition from adulthood to old age, social causation is more important than health selection (0.52 vs. 0.01), across gender and data sets. Both pathways contribute to the creation of health inequalities–however, their relative importance changes with age, which is important for understanding how health inequalities develop and how policies can address them.
Keywords: 330; Material wealth; Health inequality; Life course; Structural equation model